INTRA-RELIGIOUS DIALOGUE IN POST-SECTARIAN VIOLENCE: Assessing Sampang Sunni-Shiite Relation in Indonesia - Fiqh Vredian Aulia Ali (IAIN Ponorogo, 2018)
Abstract : While there were various studies about Sampang Shiites which explore violence, exclusion, and conflict, the study analyzing intra-religious dialogue initiative and assessing the impact of it in enhancing Sunni-Shiite resolution in post-sectarian violence in Sampang, East Java, remains understudied. For this, I use Reina Neufeldt’s framework (2011) on “the theory of change” in interfaith dialogue and employs qualitative inquiry by conducting observation, interview, and documentation. This study argues that the inability of returning Sampang Shiite to their home is in line with insufficiencies of intra-religious dialog initiatives in dealing with Sunni-Shiite antagonism theologically, facilitating reconciliation politically, and intensifying civic engagement culturally to restore social and intersect relation. However, there is a hope of peace from intersecting grassroots reconciliation between the former perpetrators and victims by “the People Peace Charter” that significantly decreased Sunni-Shiite antagonism and segregation.الملخص: على الرغم من وجود العديد من الدراسات حول سامبانج الشيعية التي تستكشف العنف والاستبعاد والنزاع ، فإن الدراسات التي تحلل مبادرات الحوار بين الأعراق وتقييم تأثيرها على تحسين حل السني و الشيعي بعد العنف الطائفي في سامبانغ ، جاوة شرق ، لم تدرس. لهذا، استخدم أطر رينا نيوفلد (2011) عن